Age-Related Characteristics as Determinants of Pragmatic Interpretation - Abdumalikova Zebiniso Allanazar qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This study examines age-related characteristics influencing pragmatic interpretation through a linguocultural-comparative analysis of English and Uzbek texts. The methodology involves analyzing linguistic expressions and pragmatic markers associated with different age groups. Findings reveal that youth in both languages is positively linked to beauty, energy, and healthiness, but negatively to immaturity and carelessness. Uzbek texts emphasize negative connotations of youth, highlighting experience and innocence, while English texts associate youth with independence and boldness. Old age in English texts often carries negative connotations, whereas Uzbek texts view it with respect and value it for experience and societal contributions. Additionally, English youth language is characterized by slang and informal expressions, while Uzbek texts depict older characters as more formal and reflective.